First cases of squirrelpox in red squirrels (Sciurus vulgaris) in Scotland. Issue 1 (11th July 2013) - McInnes, C. J.; Coulter, L.; Dagleish, M. P.; Fiegna, C.; Gilray, J.; Willoughby, K.; Cole, M.; Milne, E.; Meredith, A.; Everest, D. J.; MacMaster, A‐M.
Abstract : Squirrelpox, caused by a poxvirus, is a major threat to the remaining UK red squirrel population. The spread of antibody‐positive grey squirrels has been monitored in the UK for the past decade. In 2005 grey squirrels that had been exposed to the virus appeared in the south of Scotland for the first time, followed approximately two years later by the appearance of squirrelpox disease in the local red squirrels. Four squirrels were examined. They all had gross external lesions and histological lesions typical of squirrelpox disease, but no significant internal lesions. The diagnosis was confirmed by PCR, electron microscopy and serology.